Results of large scale media antismoking campaign in Australia: North Coast "Quit for Life" programme. Issue 6399 (15th October 1983) - Egger, G; Fitzgerald, W; Frape, G; Monaem, A; Rubinstein, P; Tyler, C; McKay, B
Abstract : A three community study was carried out in northern New South Wales, Australia, to determine the effectiveness of interventions via media and media plus community programmes in altering behaviours of life style, including smoking, dietary fat intake, and exercise. Results were analysed of one aspect of the "North Coast Healthy Lifestyle Programme" entitled "Quit for Life, " which aimed at reducing cigarette smoking over a two year period. There was a significant decline in the prevalence of smoking in both test towns, ranging from 16% in younger men to 6% in older women. These were significantly greater than the declines in the control town. The declines were more sustained over the two year period in the town subjected to media plus community programmes.